2002
DOI: 10.1021/jm010493y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Inhibitors of the Transforming Growth Factor β1 (TGF-β1) Type 1 Receptor (ALK5)

Abstract: Screening of our internal compound collection for inhibitors of the transforming growth factor beta1 (TGF-beta1) type I receptor (ALK5) identified several hits. Optimization of the dihydropyrroloimidazole hit 2 by introduction of a 2-pyridine and 3,4-methylenedioxyphenyl group gave 7, a selective ALK5 inhibitor. With this information, optimization of the triarylimidazole hit 8 gave the selective inhibitor 14, which inhibits TGF-beta1-induced fibronectin mRNA formation while displaying no measurable cytotoxicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
217
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(224 citation statements)
references
References 14 publications
7
217
0
Order By: Relevance
“…Moreover, phosphorylation and nuclear localization of Smad2 induced by TGF-β, activin, or Nodal signaling were observed in undifferentiated human ES cells, and decreased upon early differentiation [21]. Inhibition of TGF-β/activin/ Nodal signaling by SB-431542, a chemical inhibitor of the kinases of type I receptors for TGF-β/activin/Nodal [22,23], resulted in decreased expression of the markers of undifferentiated states [21,24]. Xiao et al [25] also found that activin is able to support long-term feederfree culture and maintenance of pluripotency of human ES cells possibly by inducing the expression of Oct-4 and Nanog, which was shown by microarray analysis.…”
Section: Tgf-β Family Signaling In the Maintenance Of Pluripotency Anmentioning
confidence: 99%
“…Moreover, phosphorylation and nuclear localization of Smad2 induced by TGF-β, activin, or Nodal signaling were observed in undifferentiated human ES cells, and decreased upon early differentiation [21]. Inhibition of TGF-β/activin/ Nodal signaling by SB-431542, a chemical inhibitor of the kinases of type I receptors for TGF-β/activin/Nodal [22,23], resulted in decreased expression of the markers of undifferentiated states [21,24]. Xiao et al [25] also found that activin is able to support long-term feederfree culture and maintenance of pluripotency of human ES cells possibly by inducing the expression of Oct-4 and Nanog, which was shown by microarray analysis.…”
Section: Tgf-β Family Signaling In the Maintenance Of Pluripotency Anmentioning
confidence: 99%
“…The invasion assay was conducted as described (15). EGF (60 ng/mL; Sigma) or TGF-b1 (2.5 ng/mL; R&D Systems Inc.) were used as chemoattractants, and SB-431542 (20 mmol/L; Sigma) was used as a specific TGF-b1 signaling inhibitor by blocking TbRI kinase activity (16). Cells were allowed to migrate and invade into growth factor-reduced Matrigel for 15 days, stained with 4 mmol/L calcein-acetoxymethyl ester (Invitrogen), and visualized by confocal microscopy (Leica TCS SP2 confocal microscope) using a Â10 objective.…”
Section: Cell-inverted Invasion Assaymentioning
confidence: 99%
“…Previous studies have shown that individual TbRI kinase inhibitors have different half-maximal inhibitory concentration values or different dissociation constant values for each receptor. 12,19,20 Such an inhibition profile may be due to pharmacological differences between each compound, as well as differences in receptor expression in the assayed cells. Similarly to the results of A204 cells, Ki26894 broadly suppressed the upregulation of p21 induced by myostatin, activin, and TGF-b1 in HaCaT cells.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20] A204 human rhabdomyosarcoma cells or HEK293 human embryonic kidney cells were transfected with pGL3-(CAGA) 12 luciferase, a TGF-b-sensitive Smad-responsive luciferase reporter gene. 21 Stimulation of these cells with recombinant myostatin, activin A, or TGF-b1 caused a significant increase in luciferase activity above the basal level (A204: Figure 1a-c; HEK293: Figure 1d-f).…”
Section: Tbri Kinase Inhibitors Broadly Suppress the In-vitro Transcrmentioning
confidence: 99%
See 1 more Smart Citation